The Practicalities of Educational Games: Challenges of Taking Games into Formal Educational Settings - Marklund, Bjorn Berg; Backlund, Per; Engstrom, Henrik (2014 6th International Conference on Games and Virtual Worlds for Serious Applications (VS-GAMES), 2014)
The complexity of balancing educational purpose and engaging gameplay mechanics through appropriate design decisions has frequently been discussed in learning game literature. The discussion has primarily focused on highlighting connections between game design principles and learning principles and making guidelines for achieving engaging learning scenarios through game mechanics tailored to specific subject matters. Play, and the learning derived from it, is thus often studied as a phenomenon of the two disparate forces of education and gameplay colliding inside a closed system. The complexity of designing games for educational purposes is subsequently also seen as a product of the dichotomies between these two forces. However, the discussions on the design of learning games and their potential as learning tools seldom take the practicalities of formal educational environments into consideration. In this paper, learning game design principles are investigated alongside developers' and educators' working practices. In our analysis we identify and examine a set of issues that complicate learning game design and development. The primary conclusion of this research is that the contexts in which learning games are used significantly alter the way they can be played by introducing constraints as well as facilitating conditions to the play sessions. The paper concludes with an argument for a shift of attention from the product centric view of today to a view that takes pedagogical contexts and organizational values into better account.